DILEMA KEBIJAKAN RELOKASI PEDAGANG KAKI LIMA (PKL) KE PASAR BLAURAN II KOTA SALATIGA - M. Isa Thoriq; Muchamad Samsudin (Departemen Administrasi Publik, Universitas Diponegoro, 2018)
The informal sector contributes greatly to the nation's economic development. Among the various forms of economic activity in this sector are street traders (PKL). The existence of street traders in various places has driven the economy of the community, but without good management, it will cause problems. The city of Salatiga as one of the cities in Central Java has an attraction for street traders, the existence of street traders in this city has experienced ups and downs due to the socio-economic conditions of the community. The government always regulates and manages the existence of street traders. In this case, the City Government of Salatiga through the Trade Office relocated street vendors who were on “Jalan Taman Pahlawan” to Blauran II Market. This study uses a qualitative descriptive method that looks at the problem of formulation of street traders relocation policy. Based on the conclusions of the results of this study that the incremental model of the formulation of street traders relocation has a direct impact on the street traders and the construction of Blauran II Market.